2018
DOI: 10.1037/xge0000431
|View full text |Cite
|
Sign up to set email alerts
|

Memory-guided selective attention: Single experiences with conflict have long-lasting effects on cognitive control.

Abstract: Adjustments in cognitive control, as measured by congruency sequence effects, are thought to be influenced by both external stimuli and internal goals. However, this dichotomy has often overshadowed the potential contribution of past experience stored in memory. Here, we examine the role of long-term episodic memory in guiding selective attention. Our aim was to demonstrate new evidence that selective attention can be modulated by long-term retrieval of stimulus-specific attentional control settings. All the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 116 publications
5
28
0
Order By: Relevance
“…Such a result lends some insight into how context-specific control might operate in more complex, real-world environments, where there is an over-abundance of environmental features that afford many different learned associations. From a theoretical perspective, this result is consistent memory-based accounts of CSPC phenomena (Brosowsky & Crump, 2018;J. Bugg & Hutchison, 2013;Crump & Milliken, 2009;Crump et al, , 2017.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Such a result lends some insight into how context-specific control might operate in more complex, real-world environments, where there is an over-abundance of environmental features that afford many different learned associations. From a theoretical perspective, this result is consistent memory-based accounts of CSPC phenomena (Brosowsky & Crump, 2018;J. Bugg & Hutchison, 2013;Crump & Milliken, 2009;Crump et al, , 2017.…”
Section: Discussionsupporting
confidence: 84%
“…This result is usually explained as strategic control, where participants increase attentional control under high-conflict demands and relax attentional control under low-conflict demands (Logan, 1980;Logan & Zbrodoff, 1979;Logan, Zbrodoff, & Williamson, 1984;Lowe & Mitterer, 1982). Recent work however, has demonstrated that attentional control is not only adjusted by top-down regulation, but can also be triggered automatically by environmental cues (Brosowsky & Crump, 2018;J. Bugg & Crump, 2012;Egner, 2014;Fischer & Dreisbach, 2015;King, Korb, & Egner, 2012;Mayr & Bryck, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence suggests that context-control learning is implicit (Egner, 2014;Musen & Squire, 1993) and may perhaps be considered a form of procedural memory. However, itembased context-control learning effects appear to emerge very swiftly Jacoby, Lindsay, & Hessels, 2003) or with single experiences (Brosowsky & Crump, 2018), which is not a typical characteristic of implicit/procedural learning. It is therefore plausible that control settings can be linked to contextual cues both via cumulative associative learning and via "instance-based" episodic memory processes, and that both of these learning processes might occur at the same time (Hartley & Burgess, 2005), but this possibility has not yet been explored in empirical studies.…”
Section: Remaining Challengesmentioning
confidence: 86%
“…Importantly, more recent work has demonstrated the formation of such stimulus-control associations even for a one-shot, single-exposure pairing of a stimulus and a control state (Brosowsky & Crump, 2018 ; Whitehead et al, 2020 ). This work provides evidence for an episodic memory contribution to control learning, supporting prior studies on the contextual adjustments of cognitive control that have situated their findings within an episodic control-binding framework (Dignath et al, 2019 ; Jiang et al, 2015 ; Spapé & Hommel, 2008 ).…”
Section: Introductionmentioning
confidence: 99%